Work-Life Balance in Home-Office Contexts Exploring Productivity, Stress, and Boundary Management in Remote Work - Pazer Sora (European Review Of Applied Sociology)
This study investigates the impact of home-office arrangement on work-life balance (WLB) with reference to productivity, stress, and boundary management. The study makes use of the answers of 112 participants that were collected from an online questionnaire and concludes that both the positives and negatives of working remotely prevail. While 65.2% of sample members felt more WLB and 71.5% were more productive, availability-all-the-time-causing-stress was the major issue experienced, primarily by caregivers. The study highlights the importance of technical infrastructure, boundary management tactics, and organizational support in ensuring the full potential of WLB benefits. Such conclusions guide theoretical models like Boundary Theory and the Job Demands-Resources Model and offer practical recommendations to employers and policy-makers.